Analisis Pengaruh Penanaman Modal Dalam Negeri (PMDN), Penanaman Modal Asing (PMA) Dan Produk Domestik Regional Bruto (PDRB), Terhadap Penyerapan Tenaga Kerja Di Kalimantan Barat - B01110079, MENDRI AHMED HAMBALI (Jurnal Curvanomic, 2016)
Basic problems in face indonesia in employment of this started by the high labor force indonesia a result of growth of population many cause offer labor will increase. The high offer labor not in sent with absorption of workers high have also. This study aims to analyze the influence of investment domestic, foreign capital investment and gross regional domestic product to employment in west borneo in the year 2009 to 2013.This research use the panel (cross section and time series) through a linear regression multiple regression (multiple) to technique partial least square (PLS) using the tools eviews program. Observation data about 50 in 10 district / city in west borneo during the period 2009 until 2013.The result of this research showed that investment in the country influential negative and not significantly to the absorption of labor in west borneo, foreign capital investment and influential positive significantly to the absorption of labor in west borneo, regional gross domestic product influential positive and significant against work force absorption in west borneo.Password: capital investment in the country, foreign capital investment, regional gross domestic product and employment .